Association of regional white matter hyperintensities with hypertension and cognition in the population‐based 1000BRAINS study. (22nd February 2023) - Gronewold, Janine; Jokisch, Martha; Schramm, Sara; Himpfen, Heiko; Ginster, Theresa; Tenhagen, Isabell; Doeppner, Thorsten R.; Jockwitz, Christiane; Miller, Tatiana; Lehmann, Nils; Moebus, Susanne; Jöckel, Karl‐Heinz; et al.
Abstract: Background: White matter hyperintensities of presumed vascular origin (WMH) are frequent in cerebral magnetic resonance imaging of older people. They are promoted by vascular risk factors, especially hypertension, and are associated with cognitive deficits at the group level. It has been suggested that not only the severity, but also the location, of lesions might critically influence cognitive deficits and represent different pathologies. Methods: In 560 participants (65.2 ± 7.5 years, 51.4% males) of the population‐based 1000BRAINS study, we analyzed the association of regional WMH using Fazekas scoring separately for cerebral lobes, with hypertension and cognition. Results: WMH most often affected the frontal lobe (83.7% score >0), followed by the parietal (75.8%), temporal (32.7%), and occipital lobe (7.3%). Higher Fazekas scores in the frontal, parietal, and temporal lobe were associated with higher blood pressure and antihypertensive treatment in unadjusted ordinal regression models and in models adjusted for age, sex, and vascular risk factors (e.g., age‐ and sex‐adjusted odds ratio = 1.14, 95% confidence interval = 1.03–1.25 for the association of frontal lobe WMH Fazekas score with systolic blood pressure [SBP] [per 10 mm Hg]; 1.13 [1.02–1.23] for the association of parietal lobe score with SBP; 1.72 [1.19–2.48] for the association of temporal lobe score with antihypertensive medications). In linear regressions, higher frontal lobe scores were associated with lower performance in executive function and non‐verbal memory, and higher parietal lobe scores were associated with lower performance in executive function, verbal‐, and non‐verbal memory. Conclusions: Hypertension promotes WMH in the frontal, parietal, and temporal lobe. WMH in the frontal and parietal lobe are associated with reduced executive function and memory.